2015
DOI: 10.1098/rstb.2013.0373
|View full text |Cite
|
Sign up to set email alerts
|

Ancient mitochondrial DNA from the northern fringe of the Neolithic farming expansion in Europe sheds light on the dispersion process

Abstract: The European Neolithization process started around 12 000 years ago in the Near East. The introduction of agriculture spread north and west throughout Europe and a key question has been if this was brought about by migrating individuals, by an exchange of ideas or a by a mixture of these. The earliest farming evidence in Scandinavia is found within the Funnel Beaker Culture complex (Trichterbecherkultur, TRB) which represents the northernmost extension of Neolithic farmers in Europe. The TRB coexisted for almo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 53 publications
3
66
0
1
Order By: Relevance
“…This is an unusual case of cultural transmission (Jerardino et al 2014). Other prehistoric economic transitions have been shown to be largely driven by demic diffusion (Gignoux et al 2011;Fort 2012;Skoglund et al 2014;Lazaridis et al 2014;Malmström et al 2015). Recent analysis of Europe provides a case study of demic diffusion, which appears far more complex than initially hypothesized.…”
Section: Discussionmentioning
confidence: 91%
“…This is an unusual case of cultural transmission (Jerardino et al 2014). Other prehistoric economic transitions have been shown to be largely driven by demic diffusion (Gignoux et al 2011;Fort 2012;Skoglund et al 2014;Lazaridis et al 2014;Malmström et al 2015). Recent analysis of Europe provides a case study of demic diffusion, which appears far more complex than initially hypothesized.…”
Section: Discussionmentioning
confidence: 91%
“…pottery resembling the Funnel beakers in shape. Analysis of ancient genomes from PWC and megalithic Middle Neolithic TRB context in Central Sweden has shown that PWC individuals retain the genetic signature of Mesolithic hunter-gatherers while the TRB farmers' ancestry can mainly be traced back to Central European farmers, albeit with substantial admixture from European hunter-gatherers [18][19][20] The production and use of pottery, in Central and southern Europe often seen as part of the 'Neolithic package', was already common among foragers in Scandinavia during the preceding Mesolithic Ertebølle phase. Similarly in the eastern Baltic, where foraging continued to be the main form of subsistence until at least 4,000 calBCE 15 , ceramics technology was adopted before agriculture.…”
mentioning
confidence: 99%
“…Other prehistoric economic transitions have been shown to be largely driven by demic diffusion Fort 2012;Lazaridis et al 2014;Skoglund et al 2014;Malmström et al 2015). Recent analysis of Europe provides a case study of demic diffusion, which appears far more complex than initially hypothesized.…”
mentioning
confidence: 99%